CONFLICT IN NICHOLAS SPARKS’ THE NOTEBOOK - Ratna Sari Dewi; Arifuddin Arifuddin; Afni Rosalina (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2021)
The objectives of this paper are to identify the conflicts revolving around the main characters in The Notebook, to describe and to explain how the main characters are able to deal with the conflicts in The Notebook. Conflict as a concept can explain many aspects of social life such as social disagreement, conflict of interests and fight between individuals, groups or organization. Conflict in literature refers to the different drives of the characters or forces involved. Conflict may be internal or external. This paper uses descriptive qualitative and library research methods as the topic deals with social matter, that is conflict, in a novel. Social matter is in the realm of descriptive qualitative approach so this method deserves to be applied.  The results show that there are four kinds of conflicts: man against man, man against society, man against nature, and man against self and the main cause of the conflicts is love and with love the conflicts are resolved by the main characters.